Plant Salinity Stress Response and Nano-Enabled Plant Salt Tolerance - Li, Zengqiang; Zhu, Lan; Zhao, Fameng; Li, Jiaqi; Zhang, Xin; Kong, Xiangjun; Wu, Honghong; Zhang, Zhiyong (Frontiers in Plant Science, 2022)
The area of salinized land is gradually expanding cross the globe. Salt stress seriously reduces the yield and quality of crops and endangers food supply to meet the demand of the increased population. This review summarizes the mechanisms of plant response to salt stress, including maintaining ROS (reactive oxygen species) homeostasis, regulating ion balance, and regulation at the level of plant hormones. We also discussed the molecular mechanisms involved in plant salinity stress response. Moreover, the progresses and mechanisms underlying nano-enabled plant salt tolerance were summarized and discussed. Alleviating oxidative stress damage and maintaining ion homeostasis could be the commonly employed mechanisms in nano-enabled plant salt tolerance. More mechanisms regarding nano-enabled plant salt tolerance need to be further studied.